ESTIMATES OF INTER- CHARACTER ASSOCIATION OF EASTERN COTTONWOOD (POPULUS DELTOIDES. BARTR) CLONES - AJAZ LONE,; ALTAMASH BASHIR,; SALIL K. TEWARI,; MUMTAZ MAJEED,; HILAL AHMAD2, (The Bioscan, 2013)
Forty-nine exotic and indigenous clones of Poplar were evaluated for eight morphological traits to identify the prominent clones of Poplar. At both 2 and 3 years of age diameter showed significant and positive phenotypic correlation only with plant height (0.5979) and (0.5603), respectively. Similar trend was observed with other parameters such as, at the 2 years of age Leaf lamina length showed significant and positive phenotypic correlation with petiole length (0.5447), total leaf length (0.8733), leaf width (7488), L/B ratio (0.4927). Same trend was observed at the 3rd year with Leaf lamina length being phenotypically significant and positively correlated with petiole length (0.5447), total leaf length (0.8733), leaf width (7488), L/B ratio (0.4927). Petiole length at 2 and 3 years of age was significant and positively correlated with total leaf length (0.8217) (0.8737), leaf width (0.7517 (0.5156) and L/B ratio (0.3868) (0.7317) respectively. Almost similar trend has been observed at genotypic level but with a higher degree.